Quantile-Based Extropy Measure for Record Statistics - Sharma, Salook; Kumar, Vikas (Statistics, Optimization & Information Computing, 2026)
Compared to their distribution function-based extropy measure (Lad et al. 2015), the quantile-based extropy measures have a few special characteristics (Krishnan et al. 2020). The present communication deals with the study of the quantile-based extropy measure for record statistics. In this context, a generalized model for which there is no cdf or pdf is examined, and several examples are provided for illustration purposes. Additionally, we examine the dynamic version of the suggested extropy measure for record statistics and provide characterization results for that. Finally, we investigate the suggested extropy measure in the F^{Y} family of distributions.